2020
DOI: 10.26599/jnr.2020.9040019
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells in chronic ischemic stroke: A phase 2, double-blind, randomized, controlled trial

Abstract: Olfactory ensheathing cells (OECs) have shown promising results for patients with neurologic diseases in non-double-blind, placebo control studies. Thirty patients with a unilateral ischemic stroke of more than a year were enrolled in a phase 2, multicenter, randomized, double-blind, and placebo-controlled cell therapy trial with a subsequent 12-month follow-up. The primary therapeutic objective has shown that after 12 months, there were significant differences in National Institutes of Health Stroke Scale (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…ORN and SC preparation was the same as that in our previous published paper [14]. ORN preparation and identification met the professional quality control standards of Chinese Association of Neurorestoratology (CANR; Preparatory) [15].…”
Section: Cell Preparation and Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…ORN and SC preparation was the same as that in our previous published paper [14]. ORN preparation and identification met the professional quality control standards of Chinese Association of Neurorestoratology (CANR; Preparatory) [15].…”
Section: Cell Preparation and Proceduresmentioning
confidence: 96%
“…Figure 1 shows the cell injection procedure. The procedure was the same as that used in our previous published paper [14]. Each participant was injected with 0.3 mL medium on each side of the septum with 5 × 10 6 OECs, or 5 × 10 6 SCs, or 5 × 10 6 ORNs, or 2.5 × 10 6 OECs + 2.5 × 10 6 ORNs.…”
Section: Cell Preparation and Proceduresmentioning
confidence: 99%
“…For stroke treatment, Moshayedi et al (2016) reported that as a platform to promote the adhesion of structural motifs and release of growth factors, an HA-based self-polymerizing hydrogel promoted differential maturation of NPCs in the stroke cavity and improved the survival rate of NPCs, which can be tracked by magnetic resonance imaging ( Guo et al, 2019 ; Wang et al, 2020 ).…”
Section: Stem Cells (Scs)mentioning
confidence: 99%
“…Ischemic stroke and hemorrhagic stroke in this phase are treated with the same neurorestorative therapy. The main objective is to restore the damaged neurological function and/or structure, reduce the degree of disability [52], and improve the quality of life.…”
Section: Chronic Phasementioning
confidence: 99%